The Role of Video-Based Digital Platforms in Enhancing English Speaking Skills among First Semester EFL Students - Ayu Maulidina; Julia Crist Ei Riyanti; Dhea Amelia Artikasari (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2026)
The increasing prevalence of digital platforms such as YouTube, movies, vlogs, and music has had a noteworthy influence on the oral communication skills of English Language Education Department at UIN K.H. Abdurrahman Wahid. The aim of this study is to examine the impact of frequent exposure to video-based content on students’ speaking abilities. Video learning provides a dynamic and immersive experience that enables students to hear authentic pronunciation, comprehend intonation, and observe language use in real-life contexts. Through independent and repeated consumption of various video materials, students can improve their fluency, pronunciation, and confidence in speaking. The results suggest that students who consistently engage in video-based learning demonstrate significant enhancements in their spoken language proficiency and communication aptitude. Additionally, students indicated that viewing films and videos blogs aided in their comprehension of language context and boosted their enthusiasm for learning. Video learning also offers exposure to a variety speaking styles and accents, especially those of native speakers. These results indicate that dedicating additional time to interacting with video content on digital platforms can significantly enhance speaking skills and facilitate increased engagement in the process of learning English.